UPAYA MENINGKATKAN KINERJA MELAUI MOTIVASI KERJA: REVIEW ANALISIS BIBIOMETERIX MENGGUNAKAN VOSVIEWER - Ala, Mendan (Faculty of economcs Universitas Singaperbangsa Karawang, 2024)
The aim of this research is to provide a bibliometric literature review on the role of work motivation in improving performance and see opportunities through research trends using data analysis methods using Vosviewer. Data was taken via the Google Scholar site using Publish or Perish software for 1,000 journals, then selected to become 940 articles, then the data was synchronized using Mendeley Desktop. After managing the data based it is classified and visualized using VOSviewer software. Overall, the research results show that the most publications about Motivation on employee performance in 2019 were 24 links, a total of 36 links and 68 accessories were in Cluster 2 in green, then the influence of work motivation on employee performance consisted of 6 links, 7 links and 9 occurrences. It is found in cluster 6 in light blue. So a lot of research related to work motivation has been carried out and it is necessary to examine the relationship between other factors such as: leadership style, training and compensation to avoid bias.